A composite coating for tile renovation and its preparation method and application

CN122878786APending Publication Date: 2026-10-09QINGYUAN XINGPENG NEW MATERIAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610933469.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-26
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

然而,其瓷砖面处理剂依赖有机酸和氟盐对釉面进行化学腐蚀,虽然能提高附着力,但会不可逆地损伤瓷砖表层,且酸蚀过程需要静置后再清洗,施工工序多、等待时间长,且体系中水性瓷砖改色漆为单组份丙烯酸涂料,硬度较低,机械性能仍需进一步改进

Benefits of technology

本发明用于瓷砖翻新改色的复合涂层,包括钻石瓷泥底层和罩面漆面层,底层为双组份水泥基修补材料,与瓷砖基材的热膨胀系数相近,使复合涂层在温差循环中不易产生界面应力积累,粉料以白水泥作为核心胶凝材料,遇水发生水化反应生成C-S-H凝胶和氢氧化钙晶体,构成涂层的刚性骨架;不使用传统砂子填充,而采用无砂设计,以重钙粉和钛白粉填充水泥颗粒间的微米级孔隙,调节浆料体积收缩率,提高堆积密度,同时通过钛白粉表面的活性羟基与水泥水化产物形成氢键作用,参与界面过渡区的致密化过程,提高整体致密性;纤维素醚通过长链分子上的极性基团与水分子形成氢键网络,并与淀粉醚形成物理缠结,提高浆料对水分的束缚能力,延长可施工时间,赋予浆料剪切变稀的触变特性,协同提高施工简便性;减水剂将絮凝的水泥颗粒解聚并释放被包裹的自由水,大幅降低实际水灰比,从源头上减少毛细孔生成,提高复合涂层耐水性和抗泛碱性;液料以苯丙乳液为核心,在水泥水化进行的同时脱水成膜,与C-S-H凝胶相互穿插交织,形成有机-无机互穿网络结构,赋予刚性水泥以柔韧性,吸收和分散收缩应力,堵塞水分和碱份的迁移通道,粉料与液料按2.5-3.3:1的配比混合得到底层,使体系中固相含量与液相含量达到最优平衡,通过“低水灰比+适量乳液”的设计,协同实现“高密实+高柔韧”的底层结构,提高可施工性、致密性、附着力,提高耐水性和抗泛碱性,得到性能优异的钻石瓷泥底层。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a composite coating for tile renovation and modification and a preparation method and application thereof, and comprises a diamond ceramic mud bottom layer and a topcoat surface layer; the diamond ceramic mud bottom layer is a two-component system which is formed by mixing powder and liquid according to a weight ratio of 2.5-3.3:1; the topcoat surface layer is a two-component system which is formed by mixing component A and component B according to a weight ratio of 4-6:1; the bottom layer and the surface layer are connected by the action of a dehydrating agent and a curing agent, and are chemically bonded between layers to form a unified mechanical whole; the rigid inorganic skeleton of the bottom layer provides adhesion and expansion matching; the flexible organic crosslinked network of the surface layer provides hardness and toughness, which not only guarantees long-term bonding with a tile base material, but also provides surface hardness and scratch resistance far exceeding a single coating, solves the problem that construction cannot be performed on a humid base surface, and obtains the composite coating for tile renovation and modification which is excellent in adhesion, mechanical properties, water resistance and alkali bleeding resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of building decoration technology, specifically to a composite coating for renovating and recoloring ceramic tiles, its preparation method, and its application. Background Technology

[0002] Tiles, due to their high hardness, wear resistance, and ease of cleaning, are widely used for interior and exterior wall and floor decoration. However, with the increase in the service life of tiles, as well as daily wear and tear and environmental impacts, the surface of tiles is prone to scratches, fading, wear, stain penetration, and decreased gloss, resulting in a deterioration of the overall decorative effect and affecting aesthetics and user experience. Traditional renovation methods often involve completely removing the old tiles before performing base treatment and subsequent decoration. This process is not only cumbersome and time-consuming but also generates a large amount of construction waste, leading to high renovation costs and failing to meet the requirements of green and environmentally friendly development. Therefore, the renovation technology of directly repainting and changing the color of old tiles has gradually become a research hotspot.

[0003] Currently available tile renovation and color-changing materials can be mainly divided into: solvent-based epoxy or polyurethane coatings, water-based acrylic color-changing paints, and cement-based repair materials. Solvent-based epoxy or polyurethane coatings have good adhesion and high hardness, but contain a large amount of organic solvents, resulting in a strong odor during construction, poor environmental performance, and a brittle film after curing, making them prone to cracking due to the expansion and contraction of tiles. Water-based acrylic color-changing paints use acrylic emulsions as the main film-forming agent, resulting in low odor and good environmental performance. However, due to the low hardness of acrylic resin itself and weak interfacial bonding ability, the coating film lacks scratch resistance, abrasion resistance, and adhesion, making it prone to scratches, wear, and even peeling during daily use. Cement-based repair materials are cheaper, but have limited bonding strength with tiles, and cement materials are prone to efflorescence, leading to whitening and peeling of the surface layer, and poor long-term weather resistance. In order to improve the overall performance of tile renovation and color-changing materials, recent studies have attempted to use composite systems for tile renovation and color-changing.

[0004] Chinese patent CN118995324A, "A Tile Renovation Coating System and Tile Renovation Method," discloses a tile renovation coating system comprising a tile surface treatment agent and a water-based tile color-changing paint. The tile surface treatment agent contains organic acids and fluoride salts, which clean and roughen the tile surface through a chemical reaction, improving coating adhesion. However, this tile surface treatment agent relies on organic acids and fluoride salts to chemically corrode the glaze. While this improves adhesion, it irreversibly damages the tile surface. Furthermore, the acid etching process requires a settling period before cleaning, resulting in numerous application steps and a long waiting time. Additionally, the water-based tile color-changing paint in the system is a single-component acrylic coating with low hardness, and its mechanical properties require further improvement.

[0005] Therefore, it is of great significance to develop a composite coating for tile renovation and color change that is easy to apply, causes little damage to tiles, and has high coating hardness, as well as its preparation method and application. Summary of the Invention

[0006] The purpose of this invention is to provide a composite coating for renovating and changing the color of ceramic tiles, its preparation method, and its application, so as to solve the problems mentioned in the background art.

[0007] To achieve the above objectives, the present invention provides the following technical solution: A composite coating for tile renovation and color change includes a diamond mortar base layer and a topcoat layer; The diamond porcelain clay base layer is a two-component system, composed of powder and liquid mixed in a weight ratio of (2.5-3.3):1. By weight, the powder includes: 30-50 parts white cement, 30-60 parts heavy calcium carbonate powder, 6-10 parts titanium dioxide, 0.5-2 parts cellulose ether, 0.1-0.5 parts starch ether, and 0.3-0.8 parts water-reducing agent. The liquid includes: 15-30 parts deionized water, 10-15 parts styrene-acrylic emulsion, 0.3-0.8 parts dispersant, 0.2-0.5 parts defoamer, 0.05-0.2 parts bactericide, and 0.05-0.2 parts preservative. The topcoat layer is a two-component system, consisting of component A and component B mixed in a weight ratio of (4-6):1. By weight, component A includes: 40-60 parts of hydroxyl acrylic emulsion, 20-30 parts of deionized water, 2-5 parts of diethylene glycol butyl ether, 2-5 parts of propylene glycol diacetate, 0.3-0.8 parts of wetting agent, 0.2-0.5 parts of defoamer, 0.3-0.8 parts of scratch-resistant agent, 0.2-0.8 parts of thickener, 0.1-0.3 parts of pH adjuster, and 0.1-0.3 parts of preservative. Component B includes: 20-30 parts of HDI trimer curing agent and 0.8-1.5 parts of dehydrating agent.

[0008] Preferably, the cellulose ether in the powder is hydroxypropyl methylcellulose and / or hydroxyethyl cellulose.

[0009] Preferably, the water-reducing agent in the powder is a polycarboxylate powder.

[0010] Preferably, the anti-scratch agent in component A is an organosilicon-wax composite emulsion.

[0011] Preferably, the thickener in component A is a polyurethane associative thickener and / or an alkali-swellable thickener.

[0012] Preferably, the dehydrating agent in component B is p-toluenesulfonyl isocyanate and / or an oxazolidine compound.

[0013] Preferably, the dry film thickness of the diamond ceramic clay base layer is 1-2 mm, and the dry film thickness of the topcoat layer is 40-60 μm.

[0014] In addition, the present invention also provides a method for preparing a composite coating for renovating and changing the color of ceramic tiles.

[0015] A method for preparing a composite coating for tile renovation and color change according to any one of the above-mentioned methods includes the following steps: S1. Preparation of the diamond porcelain clay base layer: White cement, heavy calcium carbonate powder, titanium dioxide, cellulose ether, starch ether, and water-reducing agent are added to a mixer in sequence and stirred evenly to obtain powder; Deionized water is added to a reaction vessel and stirred at a low speed of 200-300 rpm; Dispersant, defoamer, bactericide, and preservative are added in sequence and stirred for 2-5 minutes; Styrene-acrylic emulsion is slowly added and stirred evenly; Filter, seal and package to obtain liquid; S2. Preparation of the topcoat layer: Add deionized water to a dispersion vessel and stir at low speed (200-300 rpm). Add wetting agent, defoamer, anti-scratch agent, thickener, pH adjuster, and preservative sequentially, stirring for 3-5 minutes. Slowly add diethylene glycol butyl ether and propylene glycol diacetate, continuing to stir for 3-5 minutes. Slowly add hydroxyl acrylic emulsion while stirring, stirring for 5-15 minutes until homogeneous. Filter, seal, and package to obtain component A. Add HDI trimer curing agent to a clean container, and slowly add dehydrating agent while stirring, stirring for 3-5 minutes until completely dissolved. Seal and package to obtain component B. S3. Preparation of composite coating: Surface treatment of old ceramic tiles, mixing the powder and liquid obtained in S1 at a weight ratio of (2.5-3.3):1, stirring at 600-800 rpm for 3-5 minutes, letting stand for 2-3 minutes to mature, applying to the ceramic tile surface, and curing for 12-24 hours; then mixing component A and component B obtained in S2 at a weight ratio of (4-6):1, stirring for 1-5 minutes, letting stand to defoam, applying to the bottom layer surface, and surface drying and curing to obtain the composite coating used for ceramic tile renovation and color change.

[0016] Preferably, the mixing process described in S1 involves premixing at 300-400 rpm for 3-5 minutes, followed by mixing at 500-600 rpm for 5-15 minutes until homogeneous.

[0017] In addition, the present invention also provides an application of a composite coating for renovating and changing the color of ceramic tiles.

[0018] The application of a composite coating for renovating and changing the color of tiles according to any of the above claims is used for renovating and changing the color of old tiles.

[0019] Compared with the prior art, the beneficial effects of the present invention are: This invention relates to a composite coating for tile renovation and color change, comprising a diamond-coated mortar base layer and a topcoat layer. The base layer is a two-component cement-based repair material with a thermal expansion coefficient similar to that of the tile substrate, making the composite coating less prone to interfacial stress accumulation during temperature cycling. The powder uses white cement as the core binder, which undergoes a hydration reaction upon contact with water to generate CSH gel and calcium hydroxide crystals, forming the rigid framework of the coating. Instead of using traditional sand fillers, a sand-free design is employed, using heavy calcium carbonate powder and titanium dioxide to fill the micron-sized pores between cement particles, adjusting the slurry's volume shrinkage rate and increasing its bulk density. Simultaneously, the active hydroxyl groups on the surface of titanium dioxide form hydrogen bonds with cement hydration products, participating in the densification process of the interfacial transition zone and improving overall density. Cellulose ethers form a hydrogen bond network with water molecules through polar groups on their long-chain molecules and physically entangle with starch ethers, enhancing the slurry's ability to bind water and extending its workability. In the process, the slurry is given thixotropic properties that thin out under shear, which synergistically improves the ease of construction. The water-reducing agent deagglomerates the flocculated cement particles and releases the trapped free water, significantly reducing the actual water-cement ratio, reducing capillary formation from the source, and improving the water resistance and alkali resistance of the composite coating. The liquid material, with styrene-acrylic emulsion as the core, dehydrates and forms a film while the cement is hydrating. It interweaves with CSH gel to form an organic-inorganic interpenetrating network structure, giving rigid cement flexibility, absorbing and dispersing shrinkage stress, and blocking the migration channels of water and alkali. The powder and liquid materials are mixed at a ratio of 2.5-3.3:1 to obtain the bottom layer, so that the solid phase content and liquid phase content in the system reach the optimal balance. Through the design of "low water-cement ratio + appropriate amount of emulsion", the bottom layer structure of "high density + high flexibility" is synergistically achieved, improving workability, density, adhesion, water resistance and alkali resistance, and obtaining a high-performance diamond porcelain mortar bottom layer.

[0020] This invention relates to a composite coating for tile renovation and color change, comprising a diamond mortar base layer and a topcoat layer. The topcoat layer is a two-component polyurethane network structure, formed by chemical bonds between hydroxyl acrylic emulsion and HDI trimer curing agent to create a three-dimensional cross-linked network. Water and two slow-drying solvents are combined to form a gradient evaporation system, providing sufficient time for resin molecules to diffuse, migrate, and rearrange chains, allowing the cross-linking reaction to proceed uniformly at the molecular scale, thus improving hardness, chemical resistance, and abrasion resistance. The dehydrating agent in component B is the core technology that enables the topcoat layer to be directly applied to the cement substrate surface. By preferentially reacting with water, the dehydrating agent rapidly consumes the migrated water before the coating surface dries, generating harmless urea derivatives without producing bubbles. This creates an anhydrous environment for the subsequent main cross-linking reaction between the curing agent and hydroxyl groups, allowing the topcoat layer to be directly applied to the not-yet-dry diamond mortar base layer. This solves the problem of not being able to apply to damp substrates, greatly shortening the construction time and simplifying the process.

[0021] This invention relates to a composite coating for tile renovation and recoloring, comprising a diamond mortar base layer and a topcoat layer. During construction, the dehydrating agent first reacts with residual moisture on the surface of the base layer and in the shallow capillaries, eliminating the adverse interference of water on the curing agent. This allows some isocyanate groups in the curing agent to undergo interfacial crosslinking reactions with cement hydration products on the base layer surface and residual active hydroxyl groups in the styrene-acrylic film, in addition to crosslinking with the hydroxyl acrylic emulsion. This generates covalent bonds connecting the base layer and the top layer, forming interlayer chemical bonds, which significantly improves adhesion and overall mechanical properties. The rigid inorganic skeleton of the base layer provides adhesion and expansion matching, while the flexible organic crosslinking network of the top layer provides hardness and toughness. The highly dense base layer and the highly crosslinked dense network of the top layer together construct multiple barrier layers, synergistically improving water resistance and alkali resistance, resulting in a high-performance composite coating for tile renovation and recoloring. Detailed Implementation

[0022] To better illustrate the objectives, technical solutions, and advantages of this invention, the following embodiments are provided. Obviously, the following embodiments are only a part of the embodiments of this invention, and not all of them; these embodiments do not imply any limitation on this invention. Those skilled in the art should understand that these embodiments are only used to illustrate the technical effects of this invention, and not to limit the scope of protection of this invention.

[0023] Experimental methods in the following examples, unless otherwise specified, are generally performed under standard conditions or as recommended by the manufacturer. These examples are primarily intended to provide a better understanding of the analytical methods of this invention and do not exhaustively cover all possible procedures.

[0024] All raw materials used in the examples are commercially available; unless otherwise specified, the reagents, methods and equipment used in this invention are conventional reagents, methods and equipment in this technical field. Example 1

[0025] A method for preparing a composite coating for tile renovation and color change includes the following steps: S1. Preparation of the diamond porcelain mud base layer: 40 parts white cement, 45 parts heavy calcium carbonate powder, 8 parts titanium dioxide, 0.8 parts hydroxypropyl methylcellulose, 0.3 parts starch ether, and 0.5 parts polycarboxylate powder are added sequentially to a conical double helix mixer. First, premix at 300 rpm for 5 minutes, then stir at 500 rpm for 10 minutes until uniform. After discharge, package in a moisture-proof sealed bag to obtain the powder. Add 19 parts deionized water to a reaction vessel and stir at low speed of 300 rpm. Then, add 0.5 parts dispersant, 0.35 parts defoamer, 0.2 parts bactericide, and 0.2 parts preservative sequentially. Stir for 3 minutes, then slowly add 12 parts styrene-acrylic emulsion. Continue stirring for 5 minutes until uniform. Filter through a 100-mesh filter, seal and package to obtain the liquid. S2. Preparation of the topcoat layer: Add 25 parts of deionized water to a dispersion vessel and stir at a low speed of 300 rpm. Then, add 0.5 parts of wetting agent, 0.3 parts of defoamer, 0.6 parts of silicone-wax composite emulsion, 0.4 parts of polyurethane associative thickener, 0.2 parts of alkali-swellable thickener, 0.2 parts of pH adjuster, and 0.2 parts of preservative in sequence. Stir for 5 minutes. Slowly add 3 parts of diethylene glycol butyl ether and 3 parts of propylene glycol diacetate, and continue stirring for 3 minutes. While stirring, slowly add 55 parts of hydroxyl acrylic emulsion and stir for 10 minutes until homogeneous. Filter through a 200-mesh filter, seal and package to obtain component A. Under nitrogen protection, add 24 parts of hydrophilic HDI trimer curing agent to a clean container. While stirring, slowly add 1.2 parts of p-toluenesulfonyl isocyanate and stir for 3 minutes until completely dissolved. Seal and package to obtain component B. S3. Preparation of composite coating: Clean and degrease the surface of the old ceramic tile. Mix the powder and liquid obtained in S1 at a weight ratio of 2.9:1, stir at 600 rpm for 5 minutes until a smooth paste without particles is formed, let stand for 3 minutes to mature, and apply to the surface of the ceramic tile. The dry film thickness is 1-2 mm, and cure for 16 hours. Then, mix the components A and B obtained in S2 at a weight ratio of 5:1, stir at 600 rpm for 2 minutes, let stand for 5 minutes to defoam, and roll onto the bottom layer surface. The dry film thickness is 40-60 μm. Surface dry for 24 hours at 10-35℃ and relative humidity ≤75%, and fully cure for 7 days to obtain the composite coating used for ceramic tile renovation and color change. Example 2

[0026] A method for preparing a composite coating for tile renovation and color change includes the following steps: S1. Preparation of the diamond porcelain mud base layer: 33 parts white cement, 35 parts heavy calcium carbonate powder, 10 parts titanium dioxide, 1.5 parts hydroxypropyl methylcellulose, 0.4 parts starch ether, and 0.5 parts polycarboxylate powder are added sequentially to a conical double helix mixer. First, premix at 400 rpm for 3 minutes, then stir at 500 rpm for 10 minutes until uniform. After discharge, package in a moisture-proof sealed bag to obtain the powder. Add 15 parts deionized water to a reaction vessel and stir at 300 rpm. Then, add 0.5 parts dispersant, 0.3 parts defoamer, 0.15 parts bactericide, and 0.15 parts preservative sequentially. Stir for 3 minutes, then slowly add 10 parts styrene-acrylic emulsion. Continue stirring for 5 minutes until uniform. Filter through a 100-mesh filter, seal and package to obtain the liquid. S2. Preparation of the topcoat layer: Add 20 parts of deionized water to a dispersion vessel and stir at low speed of 300 rpm. Then, add 0.5 parts of wetting agent, 0.3 parts of defoamer, 0.5 parts of silicone-wax composite emulsion, 0.3 parts of polyurethane associative thickener, 0.2 parts of alkali-swellable thickener, 0.2 parts of pH adjuster, and 0.2 parts of preservative in sequence. Stir for 5 minutes. Slowly add 2 parts of diethylene glycol butyl ether and 2 parts of propylene glycol diacetate, and continue stirring for 3 minutes. While stirring, slowly add 42 parts of hydroxyl acrylic emulsion and stir for 10 minutes until homogeneous. Filter through a 200-mesh filter, seal and package to obtain component A. Under nitrogen protection, add 20 parts of hydrophilic HDI trimer curing agent to a clean container. While stirring, slowly add 0.8 parts of p-toluenesulfonyl isocyanate and stir for 3 minutes until completely dissolved. Seal and package to obtain component B. S3. Preparation of composite coating: Clean and degrease the surface of the old ceramic tile. Mix the powder and liquid obtained in S1 at a weight ratio of 3:1, stir at 600 rpm for 5 minutes until a smooth paste without particles is formed, let stand for 3 minutes to mature, and apply to the surface of the ceramic tile. The dry film thickness is 1-2 mm, and cure for 16 hours. Then, mix the components A and B obtained in S2 at a weight ratio of 4.5:1, stir at 600 rpm for 2 minutes, let stand for 5 minutes to defoam, and roll onto the bottom layer surface. The dry film thickness is 40-60 μm. Surface dry for 24 hours at 10-35℃ and relative humidity ≤75%, and fully cure for 7 days to obtain the composite coating used for ceramic tile renovation and color change. Example 3

[0027] A method for preparing a composite coating for tile renovation and color change includes the following steps: S1. Preparation of the diamond porcelain mud base layer: 48 parts white cement, 55 parts heavy calcium carbonate powder, 6 parts titanium dioxide, 0.5 parts hydroxyethyl cellulose, 0.3 parts starch ether, and 0.4 parts polycarboxylate powder were added sequentially to a conical double helix mixer. The mixture was premixed at 300 rpm for 5 minutes, then stirred at 600 rpm for 10 minutes until homogeneous. After discharge, the mixture was packaged in a moisture-proof sealed bag to obtain the powder. 27 parts deionized water were added to a reaction vessel and stirred at a low speed of 300 rpm. 0.5 parts dispersant, 0.4 parts defoamer, 0.2 parts bactericide, and 0.2 parts preservative were added sequentially and stirred for 3 minutes. 12 parts styrene-acrylic emulsion were slowly added and stirred for another 5 minutes until homogeneous. The mixture was then filtered through a 100-mesh filter, sealed, and packaged to obtain the liquid. S2. Preparation of the topcoat layer: Add 28 parts of deionized water to a dispersion vessel and stir at low speed of 300 rpm. Then, add 0.5 parts of wetting agent, 0.3 parts of defoamer, 0.6 parts of silicone-wax composite emulsion, 0.4 parts of polyurethane associative thickener, 0.3 parts of alkali-swellable thickener, 0.2 parts of pH adjuster, and 0.2 parts of preservative in sequence. Stir for 5 minutes. Slowly add 3 parts of diethylene glycol butyl ether and 4 parts of propylene glycol diacetate, and continue stirring for 3 minutes. While stirring, slowly add 60 parts of hydroxyl acrylic emulsion and stir for 10 minutes until homogeneous. Filter through a 200-mesh filter, seal and package to obtain component A. Under nitrogen protection, add 27 parts of hydrophilic HDI trimer curing agent to a clean container. Slowly add 1.2 parts of p-toluenesulfonyl isocyanate while stirring, and stir for 3 minutes until completely dissolved. Seal and package to obtain component B. S3. Preparation of composite coating: Clean and degrease the surface of the old ceramic tile. Mix the powder and liquid obtained in S1 at a weight ratio of 2.7:1, stir at 700 rpm for 5 minutes until a smooth paste without particles is formed, let stand for 3 minutes to mature, and apply to the surface of the ceramic tile. The dry film thickness is 1-2 mm, and cure for 15 hours. Then, mix the components A and B obtained in S2 at a weight ratio of 5.2:1, stir at 600 rpm for 2 minutes, let stand for 5 minutes to defoam, and roll onto the bottom layer surface. The dry film thickness is 40-60 μm. Surface dry at 10-35℃ and relative humidity ≤75% for 24 hours, and fully cure for 7 days to obtain the composite coating used for ceramic tile renovation and color change.

[0028] Comparative Example 1 A method for preparing a composite coating, the steps unless otherwise specified are generally the same as in Example 1, the difference being: In this comparative example, step S1 uses 10 parts of quartz sand to replace white cement.

[0029] Comparative Example 2 A method for preparing a composite coating, the steps unless otherwise specified are generally the same as in Example 1, the difference being: No water-reducing agent was added in step S1 of this comparative example.

[0030] Comparative Example 3 A method for preparing a composite coating, the steps unless otherwise specified are generally the same as in Example 1, the difference being: In this comparative example, the amount of styrene-acrylic emulsion used in step S1 was 8 parts.

[0031] Comparative Example 4 A method for preparing a composite coating, the steps unless otherwise specified are generally the same as in Example 1, the difference being: In this comparative example, the amount of styrene-acrylic emulsion used in step S1 was 18 parts.

[0032] Comparative Example 5 A method for preparing a composite coating, the steps unless otherwise specified are generally the same as in Example 1, the difference being: No dehydrating agent was added in step S2 of this comparative example.

[0033] Comparative Example 6 A method for preparing a composite coating, the steps unless otherwise specified are generally the same as in Example 1, the difference being: In this comparative example, the weight ratio of the diamond porcelain clay base powder to the liquid material in step S3 is 2.2:1.

[0034] Comparative Example 7 A method for preparing a composite coating, the steps unless otherwise specified are generally the same as in Example 1, the difference being: In this comparative example, the weight ratio of the diamond porcelain clay base powder to the liquid material in step S3 is 3.5:1.

[0035] Comparative Example 8 A method for preparing a composite coating, the steps unless otherwise specified are generally the same as in Example 1, the difference being: In this comparative example, the weight ratio of component A to component B in the topcoat layer of step S3 is 3:1.

[0036] Comparative Example 9 A method for preparing a composite coating, the steps unless otherwise specified are generally the same as in Example 1, the difference being: In this comparative example, the weight ratio of component A to component B in the topcoat layer of step S3 is 7:1.

[0037] Comparative Example 10 A method for preparing a composite coating, the steps unless otherwise specified are generally the same as in Example 1, the difference being: In this comparative example, no dehydrating agent is added in step S2, and the weight ratio of component A to component B in the topcoat layer in step S3 is 7:1.

[0038] Comparative Example 11 A method for preparing a composite coating, the steps unless otherwise specified are generally the same as in Example 1, the difference being: This comparative model only shows the diamond porcelain clay base layer.

[0039] Comparative Example 12 A method for preparing a composite coating, the steps unless otherwise specified are generally the same as in Example 1, the difference being: This comparative example only shows the topcoat layer.

[0040] The composite coatings obtained in Examples 1-3 and Comparative Examples 1-12 were applied to the surface of the same batch of old ceramic tiles (300mm×300mm, glazed tiles) according to their respective S3 steps. The dry film thickness of the bottom layer was controlled at 1.5±0.2mm, and the dry film thickness of the top layer was controlled at 50±5μm. All samples were cured under standard curing conditions (temperature 23±2℃, relative humidity 50±5%) for 14 days before performance testing. Five samples were taken for each test group, and the average value was taken. The specific testing method is as follows: Workability and Coating Appearance During the S3 step of troweling and roller coating, the same operator records the troweling feel, leveling properties, and sagging of the slurry. After the coating is fully cured, the surface condition is visually observed in a standard light source box (D65 light source), with a focus on checking for defects such as pinholes, bubbles, cracks, and shrinkage cavities. The bubble density is counted and tallied as the number of bubbles per square meter.

[0041] Adhesion The adhesion was tested according to GB / T 5210-2006 "Paints and Varnishes - Pull-off Test". A 20mm diameter aluminum alloy test column was used, bonded to the coating surface with epoxy resin adhesive. After the adhesive had fully cured, an adhesion tester was used to apply a vertical pull at a loading rate of 10mm / min. The maximum pull force when the coating detached from the tile substrate was recorded, and the adhesion strength (MPa) was calculated.

[0042] hardness The test was conducted according to GB / T 6739-2006 "Determination of Hardness of Paints and Varnishes by Pencil Method". The pencil was held at a 45° angle to the coating surface and advanced about 1 cm at a speed of about 1 cm / s. Pencils of different hardnesses were used to scratch the coating surface in sequence. The lowest hardness grade at which a visible scratch or abrasion just appeared on the coating surface was taken as the test result.

[0043] Scratch resistance Referring to the principles of ISO 15695:2000 "Determination of scratch resistance of paints and varnishes" and GB / T 9279.1-2015 "Determination of scratch resistance of paints and varnishes—Part 1: Constant load method", #0000 steel wool was used to rub the coating surface repeatedly at a rate of 60 times / minute under a load of 500g, with a reciprocating stroke of 50mm. The coating surface was observed after every 50 reciprocations, and the number of reciprocations at which three or more consecutive visible scratches first appeared on the surface was taken as the scratch resistance index.

[0044] Water resistance The test was conducted according to Method A of GB / T 1733-1993 "Determination of Water Resistance of Paint Film". Two-thirds of the sample area was immersed in distilled water at (23±2)℃ for 96 hours. After removal, the surface moisture was blotted with filter paper, and the paint film was immediately visually observed under diffused sunlight to check for phenomena such as blistering, peeling, discoloration, loss of gloss, or softening.

[0045] Anti-alkali The test was conducted according to GB / T 9265-2009 "Determination of Alkali Resistance of Architectural Coatings". A saturated calcium hydroxide solution was prepared, and two-thirds of the sample area was immersed in saturated lime water at (23±2)℃ for 72 hours. After removal, the surface was gently rinsed with running water and visually observed under diffused sunlight, focusing on whether white efflorescence (alkali efflorescence), blistering, or peeling appeared on the coating surface. The sample was then placed in a constant temperature and humidity chamber at (40±2)℃ and (85±5)% relative humidity for accelerated curing for 28 days, and the surface of the coating was observed for the precipitation of white salts.

[0046] The specific test results of Examples 1-3 and Comparative Examples 1-12 are shown in the table below: Table 1 Performance test results of Examples 1-3 and Comparative Examples 1-12 As shown in Table 1, the composite coatings for tile renovation and color change prepared in Examples 1-3 of this invention all have excellent comprehensive performance, suitable viscosity, smooth and non-sticky texture, easy construction, and smooth surface without pinholes or bubbles. The cement-based diamond porcelain mortar base layer can easily repair tile gaps, chipped corners, and unevenness, ensuring a smooth fit with the tile without damaging the glaze. It poses no risk of corrosion to areas where construction is not required, has an adhesion strength ≥1.7MPa, and the cement base and tile have matching thermal expansion, ensuring stable and reliable long-term adhesion. The topcoat layer contains a dehydrating agent, allowing direct application onto a cement base that is not completely dry, forming a high-crosslink density polyurethane network. The surface is smooth and does not bubble, the coating hardness reaches 2H, the scratch resistance reaches more than 150 times, and the water resistance and alkali resistance are excellent. It does not bubble, peel, whiten, or effloresce, and has excellent industrial application value.

[0047] In Comparative Example 1, 10 parts of quartz sand were used to replace white cement. Quartz sand has advantages in conventional cement-based repair systems, such as aggregate skeleton, improved wear resistance, and crack resistance. However, in this scheme, quartz sand is an inert hard particle that does not participate in the cement hydration reaction. Its surface is smooth and has no cementitious activity, so it cannot form a strong chemical bond with cement hydration products. It exists in the hard body only through mechanical interlocking. As a hard point, it disrupts the continuity of the slurry, which reduces the effective contact area between the coating and the tile interface. The adhesion drops sharply to 0.95 MPa. Microcracks and pores exist in the interface transition zone between the particles and the cement slurry, which become rapid channels for the migration of moisture and alkali. The resistance to efflorescence, especially the long-term resistance to efflorescence, is severely reduced. Other properties are also comprehensively deteriorated due to the interface defects caused by the introduction of sand particles. This proves the necessity of the sand-free filler design in this invention compared with conventional cement-based repair systems.

[0048] In Comparative Example 2, without the addition of water-reducing agent, the actual water requirement of the cement paste increased significantly in order to achieve a trowelable consistency. The water-cement ratio increased, and after hardening, the excess water evaporated, leaving a large number of capillary channels. This resulted in a severe decrease in the density of the composite coating. Moisture and alkali could quickly migrate to the surface through the capillaries, causing severe whitening of the surface. The capillaries weakened the strength of the coating itself, and at the same time, the precipitation of alkali at the interface damaged the adhesion, reducing the adhesion to 1.12 MPa.

[0049] In Comparative Example 3, the amount of styrene-acrylic emulsion was reduced to 8 parts. The polymer film could not continuously cover the entire capillary network of the cement stone, leaving a large number of unclosed interconnected pores. The resistance to alkali efflorescence decreased, and the continuous migration of moisture and alkali destroyed the chemical bonding of the interface layer, resulting in an adhesion strength of 1.21 MPa.

[0050] In Comparative Example 4, the amount of styrene-acrylic emulsion was increased to 18 parts. The total amount of emulsion exceeded the saturation adsorption capacity of the cement particle surface and capillary pores. The excess emulsion was free in the slurry system, which significantly increased the viscosity of the slurry. During application, the trowel stuck to the surface severely, reducing the construction efficiency. The excessively thick polymer film formed a weak boundary layer at the interface, which weakened the direct chemical bonding between the cement hydration products and the tile surface. The adhesion dropped to 1.56 MPa. Moreover, the increased amount of emulsion significantly increased the cost of raw materials.

[0051] Comparative Examples 2, 3, and 4 collectively demonstrate the necessity of the present invention in using "low water-cement ratio + appropriate amount of emulsion" to improve density and adhesion, inhibit efflorescence, and prevent cracking.

[0052] In Comparative Example 5, without the addition of a dehydrating agent, the isocyanate groups in the HDI trimer curing agent directly reacted with the residual free and bound water in the undried cement-based diamond mortar substrate, generating numerous bubbles. These bubbles formed pinholes and bubble defects within the paint film or at the substrate-top layer interface, significantly reducing the effective bonding area at the interface. Adhesion plummeted to 0.84 MPa. The bubbles also became channels for the penetration of moisture and corrosive media. Although no significant bubbling was observed in the water resistance, numerous pinholes were present, leading to a significant deterioration in long-term water resistance. This demonstrates the necessity of the present invention, which incorporates a dehydrating agent that preferentially reacts with moisture to consume free water, fundamentally eliminating the basis for bubble formation and improving adhesion and water resistance.

[0053] Comparative Example 6 reduced the mixing ratio of powder to liquid to 2.2:1, resulting in a significant increase in the actual water-cement ratio. The excessively thin slurry would sag noticeably under its own weight when applied to vertical surfaces, leading to poor controllability during construction. Excessive water would evaporate after hardening, forming numerous capillary pores and shrinkage voids, significantly increasing the drying shrinkage rate. Shrinkage stress would concentrate at weak interfaces, causing numerous microcracks in the interface layer, severe efflorescence on the surface, and significant deterioration in all properties.

[0054] Comparative Example 7 increased the mixing ratio of powder to liquid to 3.5:1. The free water content in the slurry system was too low, and the cement particles could not be fully hydrated. The resistance during application was extremely high, making the operation laborious and difficult to smooth, resulting in low construction efficiency. When the dry and hard slurry came into contact with the smooth tile interface, it was not sufficiently wetted and spread. At the microscopic scale, there were a large number of unfilled interfacial voids, resulting in insufficient interfacial bonding. The adhesion by the pull-out method was only 1.18 MPa. Due to insufficient hydration, a small amount of efflorescence occurred, and the surface was slightly whitened.

[0055] Comparative Examples 6 and 7 together demonstrate that the present invention selects a powder-to-liquid ratio within the range of (2.5-3.3):1, which balances workability and final performance.

[0056] In Comparative Example 8, the mixing ratio of component A to component B in the topcoat was reduced to 3:1. The isocyanate groups in the system were relatively excessive, exceeding the dehydrating agent's processing capacity. Some of them reacted with water to generate bubbles, while others underwent self-polymerization to form urea and biuret structures. As a result, although the crosslinking density of the paint film was very high, the crosslinking network was unevenly distributed, and the local over-crosslinked areas were brittle. The pencil hardness reached 2H, but the scratch resistance decreased to 130 times, and the adhesion was only 1.43 MPa, making it more prone to brittle fracture.

[0057] Comparative Example 9 increased the mixing ratio of component A to component B of the top layer to 7:1. The HDI trimer curing agent was relatively insufficient, and some hydroxyl groups in the system failed to participate in the cross-linking reaction. They only existed in the paint film in a physical entanglement manner. The overall cross-linking network structure was loose, the scratch resistance was significantly reduced, and the adhesion dropped to 1.31 MPa.

[0058] Comparative Examples 8 and 9 together demonstrate that the present invention selects a mixing ratio of component A to component B of (4-6):1 to ensure that the curing agent matches the functional groups in the system, forming a dense and uniform cross-linked network, which is necessary to comprehensively improve hardness, scratch resistance and long-term durability.

[0059] Comparative Example 10, without adding a dehydrating agent and increasing the A / B ratio of the topcoat to 7:1, resulted in a relative deficiency of the curing agent, low crosslinking density of the paint film, and slow film formation speed. The coating remained in a flowing or semi-cured state for a longer period. Residual moisture in the cement substrate continued to migrate upwards and react with the curing agent, generating numerous bubbles. This created a vicious cycle: slow film formation allowed bubbles more time to push up the paint film, and the low crosslinking density meant the paint film strength was insufficient to restrain bubble expansion. Ultimately, the paint film exhibited dense bubbles, with large areas of the paint film bulging and peeling off. Adhesion dropped to 0.52 MPa, with severe blistering and efflorescence, resulting in the most severe performance degradation. This demonstrates the necessity of the present invention's reasonable component ratio and dehydrating agent design, enabling direct application to undried cement substrates, significantly shortening construction time and simplifying the process.

[0060] Comparative Example 11 only retained the diamond porcelain clay base layer without applying a topcoat. Lacking the interfacial cross-linking reaction between the polyurethane topcoat and the base layer surface, and lacking a chemical cross-linking network, it could not effectively resist indentation and scratches. Adhesion dropped to 1.36 MPa, pencil hardness was only grade B, and scratch resistance was only 50 times. Without the protection of the topcoat, the base layer was directly exposed to the environmental medium, exhibiting severely insufficient water and alkali resistance, manifesting as severe whitening, blistering, and slight whitishness. This demonstrates that the topcoat layer of this invention is a key barrier preventing water vapor penetration and protecting the cement substrate.

[0061] Comparative Example 12 involved applying only the topcoat directly to the surface of an old ceramic tile without a diamond-coated ceramic mortar underlayer. This resulted in insufficient chemical adsorption and mechanical anchoring points on the smooth glazed surface, leading to inadequate overall composite strength. The adhesion was only 0.42 MPa, and the scratch resistance was only 90 cycles. After a water resistance test, moisture penetrated the interface, causing large-area peeling of the topcoat and complete loss of adhesion. This demonstrates that the diamond-coated ceramic mortar underlayer of this invention not only provides adhesion but also, through its slightly rough surface and chemical bonding with the topcoat, effectively transfers stress from the topcoat to the underlayer and the ceramic tile, playing a crucial role in overall synergistic load-bearing.

[0062] In summary, the composite coating for tile renovation and color change of the present invention includes a diamond mortar base layer and a topcoat layer. The base layer and the topcoat layer are connected by the action of a dehydrating agent and a curing agent. The interlayer chemical bonds form a unified mechanical whole. The rigid inorganic skeleton of the base layer provides adhesion and expansion matching, while the flexible organic cross-linked network of the topcoat layer provides hardness and toughness. This ensures long-term adhesion to the tile substrate and provides surface hardness and scratch resistance far exceeding that of a single coating. As a result, a composite coating for tile renovation and color change with excellent adhesion, mechanical properties, water resistance and efflorescence resistance is obtained.

[0063] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A composite coating for renovating and recoloring ceramic tiles, characterized in that: Including the diamond ceramic clay base layer and the topcoat layer; The diamond porcelain clay base layer is a two-component system, which is composed of powder and liquid mixed in a weight ratio of (2.5-3.3):1; By weight, the powder comprises: 30-50 parts white cement, 30-60 parts heavy calcium carbonate powder, 6-10 parts titanium dioxide, 0.5-2 parts cellulose ether, 0.1-0.5 parts starch ether, and 0.3-0.8 parts water-reducing agent; the liquid comprises: 15-30 parts deionized water, 10-15 parts styrene-acrylic emulsion, 0.3-0.8 parts dispersant, 0.2-0.5 parts defoamer, 0.05-0.2 parts bactericide, and 0.05-0.2 parts preservative. The topcoat layer is a two-component system, consisting of component A and component B mixed in a weight ratio of (4-6):

1. By weight, component A includes: 40-60 parts of hydroxyl acrylic emulsion, 20-30 parts of deionized water, 2-5 parts of diethylene glycol butyl ether, 2-5 parts of propylene glycol diacetate, 0.3-0.8 parts of wetting agent, 0.2-0.5 parts of defoamer, 0.3-0.8 parts of scratch-resistant agent, 0.2-0.8 parts of thickener, 0.1-0.3 parts of pH adjuster, and 0.1-0.3 parts of preservative. Component B includes: 20-30 parts of HDI trimer curing agent and 0.8-1.5 parts of dehydrating agent.

2. The composite coating for tile renovation and color change according to claim 1, characterized in that: The cellulose ether in the powder is hydroxypropyl methylcellulose and / or hydroxyethyl cellulose.

3. The composite coating for tile renovation and color change according to claim 1, characterized in that: The water-reducing agent mentioned in the powder is polycarboxylate powder.

4. The composite coating for tile renovation and color change according to claim 1, characterized in that: The anti-scratch agent in component A is an organosilicon-wax composite emulsion.

5. A composite coating for tile renovation and color change according to claim 1, characterized in that: The thickener in component A is a polyurethane associative thickener and / or an alkali-swellable thickener.

6. A composite coating for tile renovation and color change according to claim 1, characterized in that: The dehydrating agent in component B is p-toluenesulfonyl isocyanate and / or oxazolidine compounds.

7. A composite coating for tile renovation and color change according to claim 1, characterized in that: The dry film thickness of the diamond ceramic clay base layer is 1-2 mm, and the dry film thickness of the topcoat layer is 40-60 μm.

8. A method for preparing a composite coating for tile renovation and color change according to any one of claims 1-7, characterized in that, Includes the following steps: S1. Preparation of the diamond porcelain clay base layer: White cement, heavy calcium carbonate powder, titanium dioxide, cellulose ether, starch ether, and water-reducing agent are added to a mixer in sequence and stirred evenly to obtain powder; Deionized water is added to a reaction vessel and stirred at a low speed of 200-300 rpm; Dispersant, defoamer, bactericide, and preservative are added in sequence and stirred for 2-5 minutes; Styrene-acrylic emulsion is slowly added and stirred evenly; Filter, seal and package to obtain liquid; S2. Preparation of the topcoat layer: Add deionized water to a dispersion vessel and stir at low speed (200-300 rpm). Add wetting agent, defoamer, anti-scratch agent, thickener, pH adjuster, and preservative sequentially, stirring for 3-5 minutes. Slowly add diethylene glycol butyl ether and propylene glycol diacetate, continuing to stir for 3-5 minutes. Slowly add hydroxyl acrylic emulsion while stirring, stirring for 5-15 minutes until homogeneous. Filter, seal, and package to obtain component A. Add HDI trimer curing agent to a clean container, and slowly add dehydrating agent while stirring, stirring for 3-5 minutes until completely dissolved. Seal and package to obtain component B. S3. Preparation of composite coating: Surface treatment of old ceramic tiles, mixing the powder and liquid obtained in S1 at a weight ratio of (2.5-3.3):1, stirring at 600-800 rpm for 3-5 minutes, letting stand for 2-3 minutes to mature, applying to the ceramic tile surface, and curing for 12-24 hours; then mixing component A and component B obtained in S2 at a weight ratio of (4-6):1, stirring for 1-5 minutes, letting stand to defoam, applying to the bottom layer surface, and surface drying and curing to obtain the composite coating used for ceramic tile renovation and color change.

9. A method for preparing a composite coating for tile renovation and color change according to claim 8, characterized in that: The mixing process described in S1 involves first premixing at 300-400 rpm for 3-5 minutes, then mixing at 500-600 rpm for 5-15 minutes until homogeneous.

10. The application of a composite coating for tile renovation and color change according to any one of claims 1-7, characterized in that: Used for renovating and changing the color of old tiles.

Citation Information

Patent Citations

  • Ceramic tile renovating coating system and ceramic tile renovating method

    CN118995324A